RESPONSE OF DIFFERENT AVOCADO MICROCLONAL ROOTSTOCK VARIETIES TO ETIOLATION TIME (Nativa, 2024)
The potential impact of uniform, consistent, rapid, easy-to-transport, and disease-free clonal propagation of avocado (Persea americana Mill.) is significant for the industry. This research, conducted with a meticulous Split Plot arrangement in a Completely Randomized Design, provides valuable insights into optimizing microcloning techniques for avocado clonal propagation, specifically regarding varietal responses to etiolation time for more efficient and productive avocado cultivation. The study investigated the response of clonal rootstocks to etiolation as a means of microcloning, using different lengths of etiolation time (0, 2, 4 and 6 weeks) as the main plots and three clonal varieties of avocado rootstocks (‘Malagkit’, ‘Evergreen’, and ‘Hass’) as the subplots. Results revealed an interaction effect in leaf chlorophyll content, with ‘Hass’ rootstocks etiolated for six weeks exhibiting the highest value of 41.59 SPAD. Individually, ‘Hass’ rootstocks demonstrated superior performance in various parameters, including stem length (9.97 cm), stem diameter (.3880 cm), and leaf number (8.37). The ‘Evergreen’ clonal rootstocks exhibited the largest leaf area (53.54 cm2) and the darkest leaf (4.82) and stem (5.00) color. The findings suggest significant variability among the three avocado clonal rootstock varieties in response to etiolation time. Specifically, ‘Hass’ rootstocks performed optimally when etiolated for four to six weeks.Keywords: clonal rootstocks; disease-free propagation; microcloning. Resposta de diferentes variedades de porta-enxertos microclonais de abacateiro ao tempo de etiolamento RESUMO: O potencial impacto da propagação clonal uniforme, consistente, rápida, fácil de transportar e livre de doenças do abacateiro (Persea americana Mill.) é significativo para a indústria. Esta pesquisa fornece informações valiosas para otimizar técnicas de micropropagação para propagação clonal de abacateiros, especificamente as respostas varietais ao tempo de etiolamento para uma cultivação de abacateiros mais eficiente e produtiva. Este estudo, utilizando um arranjo de Parcela Dividida em um Design Completamente Aleatório, investigou a resposta de porta-enxertos clonais ao etiolamento como meio de micropropagação. A pesquisa utilizou diferentes períodos de etiolamento (0, 2, 4, 6 semanas) como parcelas principais e três variedades clonais de porta-enxertos de abacateiro ('Malagkit', 'Evergreen' e 'Hass') como subparcelas. Os resultados revelaram um efeito de interação no teor de clorofila foliar, com os porta-enxertos 'Hass' etiolados por seis semanas apresentando o maior valor de 41.59 SPAD. Individualmente, os porta-enxertos 'Hass' demonstraram desempenho superior em vários parâmetros, incluindo comprimento do caule (9.97 cm), diâmetro do caule (0.3880 cm) e número de folhas (8.37). Os porta-enxertos clonais 'Evergreen' exibiram a maior área foliar (53.54 cm2) e a cor mais escura de folhas (4.82) e caules (5.00). No geral, os resultados sugerem uma variabilidade significativa entre as três variedades clonais de porta-enxertos de abacateiro em resposta ao tempo de etiolamento. Especificamente, os porta-enxertos 'Hass' apresentaram desempenho ótimo quando etiolados por quatro a seis semanas.Palavras-chave: porta-enxertos clonais; propagação livre de doenças; microclonagem.